Mass spectrometry footprinting reveals how kinetic stabilizers counteract transthyretin dynamics altered by pathogenic mutations - Francisca Pinheiro; Ravi Kant; Saketh Chemuru; Nathalia Varejão; Adrián Velázquez-Campoy; David Reverter; Irantzu Pallarès; Michael L. Gross; Salvador Ventura (Proceedings of the National Academy of Sciences, 2026)
The aggregation of transthyretin (TTR) results in life-threatening transthyretin amyloidosis. Familial forms of the disease arise from point mutations that destabilize the TTR tetramer, leading to its dissociation and/or monomer unfolding and subsequent formation of amyloid fibrils. Small molecules that kinetically stabilize the native tetramer effectively inhibit this aggregation. Although over 300 X-ray crystal structures of TTR have been determined, these data refer to a static structure and do not capture the conformational effects of mutations and ligand binding. Here, we demonstrate that hydrogen–deuterium exchange (HDX) and fast photochemical oxidation of proteins (FPOP) coupled with mass spectrometry (MS) offer critical insights into the conformational dynamics associated with TTR amyloidogenic mutations and the binding of kinetic stabilizers. The results indicate that the design of TTR binders should consider the specific conformational traits of each TTR pathogenic variant. We propose that incorporating MS-based techniques into TTR drug discovery will expedite the development of effective pathology-specific aggregation inhibitors.